A longitudinal analysis of work-life balance perspectives of future business professionals. (2015) - Linnhoff, Stefan; Smith, Katherine Taken; Smith, L. Murphy
People face the difficulty of how to allocate their limited time between work and non-work activities; this is the age-old problem of work-life balance. Facilitating work-life balance for its employees is a vital aspect of best practices in business management, which will engender higher levels of employee job performance and ethical behaviour. This study compares findings of prior research with results of a current survey of work-life balance perspectives of future business professionals. A key finding is that work-life balance is still of high importance. In addition, some interesting gender-related changes were observed. Comparing the results for 2013 and 2008, findings show that regarding WLB-related issues that were of more concern to females than males in the past are now essentially of shared interest for both sexes.